Sustainability Accounting Concept in Higher Education Institution: A Case Study of an Indonesian Public University - Kurniawan, Putu Sukma (Jurnal Ilmiah Akuntansi dan Bisnis, 2020)
The change in the accounting paradigm has now shifted from conventional accounting to sustainability accounting. This study seeks to develop a model for implementing sustainability accounting in educational sector organizations. The object of this research is the Universitas Pendidikan Ganesha, Bali. This research used a qualitative approach. This research is divided into two main stages. The first stage is the stage of observation regarding the current accounting system. At this stage, data will be searched for the development of the sustainability accounting implementation model. The method of collecting data in the first stage is to conduct interviews, observation, and document analysis. The second stage is the stage for designing the sustainability accounting implementation model. The output of this research is a concept or model regarding the application or implementation of sustainability accounting in the activities of educational sector organizations. The results of this study are expected to provide guidelines for educational sector organizations (universities) in the context of applying sustainability accounting concept.